The Development of Kinemaster Animation Video as a Media to Improve Science Literacy in Elementary Schools - Abdul Rochman Amrullah; Suryanti Suryanti; Nadi Suprapto (University of Bengkulu, 2022)
The research was conducted to develop kinemaster animation video media using the four D development model to improve students' scientific literacy on magnetism. The aim of this study was the Kinemaster animated video media that tried out to 27 six-grade students of SDN Bulusidokare Sidoarjo with Control Group Pretest-Posttest Design. Data collection techniques were validation, observation, tests, and questionnaire. The analysis of research result revealed that the feasibility included: 1) valid, the media and instructional tools that were developed by the researchers were feasible to be experimented; 2) practical, the feasibility of learning went very well with the percentage of 88% to 100%, best practice that was found were students’ enthusiasm increased, the media could be played many times and able to motivate students in doing experiments. The obstacles that happened during the learning process were students’ readiness, insubstantial facilities and infrastructure, and nonoptimal online learning supervision; 3) effective, the science-literacy-test result of experimental-class students passed with N-gain 0,5 to 1,0. Whereas on the control-class, some students faced failure with N-gain 0,17 to 0,57. Data from N-gain results (%) both classes got normal and homogenous distribution, thus independent sample t-test was conducted with significance result 0,00 < 0,05. It can be affirmed that there was effectivity difference in improving science literacy on experimental-class and control-class. Good responses that students gave reached 89% to 100%. The conclusion of this study is Kinemaster animated video media was feasible and effective to be used in improving science literacy on primary school students.